ANALISIS HUKUM PEMISAHAN UNIT USAHA SYARIAH MENJADI PERUSAHAAN ASURANSI SYARIAH - Ahmad Supyan Ritonga (Adpertens: Jurnal Ekonomi dan Manajemen, 2024)
Conventional sharia insurance and insurance have fundamental differences. Although sharia insurance started from one unit of a conventional company as its parent. As a separate unit, sharia offers products that are certainly different from conventional insurance and are based on sharia provisions. Where it is isolated from the practices of gharar, maisir and usury. For this reason, it is necessary to separate the sharia insurance business unit into a Sharia Insurance Company (Full Flegde). With the aim of increasing the increasingly rapid growth of insurance. The prospects for a Sharia Insurance Company split (Spin Off) include: Insurance development is considered to be more competitive, improves the quality of trust and image, increases productivity and efficiency, improves the capital structure, provides benefits for shareholders, supports public trust in sharia insurance